Philosophical-Psychological Approach to Culture and Education - sandeep sandeep; Ponung Nonang (Journal of Philosophical Investigations, 2023)
Education is a continually developing activity, it shapes the way an individual develops their attitudes, thoughts and behavior. Education is not just about being literate but it is an overall development of the person in every aspect of their lives. A society's educational system can be greatly linked to its culture as the culture that one is in have an affect on the type of curriculum the institutions will develop in order to cater to every individual of that particular culture. Education moulds and shapes a society and it is influenced by the culture of the particular country or society. The educational system acts as a point of reference for the society's needs and demands. The principles that dominate this article is culture and education are interrelated and interconnected. Every educational paradigm is influenced by the culture of the society in which it operates. This essay underlines the extensive connection between culture and education. As a result, the goal of this essay is to depict these features from a Philosophical-Psychological Approach.